Postbiotic of Pediococcus acidilactici GQ01, a Novel Probiotic Strain Isolated from Natural Fermented Wolfberry, Attenuates Hyperuricaemia in Mice through Modulating Uric Acid Metabolism and Gut Microbiota - Lu Ren; Shangshang Wang; Shiting Liu; Hetti Arachchige Chalani Prasanthi; Yuechan Li; Jun Cao; Feiliang Zhong; Le Guo; Fuping Lu; Xuegang Luo (Foods, 2024)
Hyperuricaemia (HUA) is a disorder of purine metabolism, which manifests itself as an increase in uric acid production and a decrease in uric acid excretion, as well as a change in the structure of the intestinal microbiota. Most of the drugs currently used to treat HUA have significant side effects, and it is essential to find a treatment for HUA that is free of side effects. In this study, a novel strain, Pediococcus acidilactici GQ01, was screened from natural fermented wolfberry. The effects of both live bacteria GQ01 and its heat-killed G1PB postbiotic on HUA were investigated. The results showed that both probiotic GQ01 and G1PB postbiotics could effectively decrease blood uric acid, creatinine, and urea nitrogen levels in the HUA mice model. P. acidilactici GQ01 was more effective in inhibiting ADA activity, while G1PB postbiotics was more effective in inhibiting XOD activity. Meanwhile, GQ01 and G1PB were able to ameliorate liver and kidney tissue injury, upregulate the expression of ABCG2 in kidney and XOD gene in liver, downregulate the protein expression of URAT1 and GLUT9 in kidney, and therefore reduce the value of blood uric acid by decreasing the uric acid reabsorption and increasing the excretion of uric acid. Additionally, both probiotics and postbiotics could regulate the intestinal microbiota structure of HUA mice, so as to bring the dysfunctional intestinal composition back to normal. Furthermore, P. acidilactici GQ01 and G1PB postbiotics can increase the levels of acetic acid, propionic acid, and butyric acid in the intestinal tract, improve the intestinal function, and maintain the healthy homeostatic state of the intestinal tract. In summary, P. acidilactici GQ01 and its G1PB postbiotics may be developed as functional food or drug materials capable of treating HUA.